Material Testing 2.0: A brief review - Pierron, Fabrice (Strain, 2023)
With the advent of camera‐based full‐field measurement techniques such as digital image correlation (DIC), researchers have been trying to exploit such rich data sets through the use of more complex test configurations than the standard ones (uniaxial tension/compression, bending etc.). This new paradigm in mechanical testing of materials has recently been christened ‘Material Testing 2.0’. This paper provides a brief overview of this field, which is currently seeing a large increase in research effort.